Верховенство права, правова культура, освіта й академічна доброчесність - Дуліба, Є. В.; Duliba, Ye. V.; Аврамова, О. Є.; Avramova, O. Y.; Куліш, А. М.; Kulish, A. M.; Миргород-Карпова, В. В.; Myrhorod-Karpova, V. V. (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 3 (98). – С. 15-25, 2022)
Проаналізовано Рейтинг верховенства права за 2021 рік, Рейтинг процвітання за 2021 рік, Рейтинг рівня освіти за країнами 2021 року, світові рейтинги університетів (Times Higher Education за 2021 рік, QS World University Rankings 2021), продемонстровано існування чіткої кореляції між дотриманням принципу верховенства права в державі та правовою культурою, освітою і дотриманням академічної доброчесності. Доведено, що чим вищий рівень дотримання принципу верховенства права, тим вищий рівень правової культури та відповідно рівень і якість освіти та дотримання академічної доброчесності. Висвітлено актуальні проблеми академічної доброчесності в Україні та запропоновано шляхи їх вирішення.

Comparing the 2021 Rule of Law Index, 2021 Legatum Prosperity Index, 2021 Education Rankings by Country, 2021 Times Higher Education, 2021 QS World University Rankings has demonstrated that there is a clear correlation between adherence to the rule of law in the state and the legal culture, education and academic integrity. It is proved that the higher the level of adherence to the rule of law, the higher is the level of legal culture and, accordingly, the level of quality of education and observance of academic integrity. The issues of academic integrity are issues of each country, but the factors influencing academic integrity differ significantly between countries, between different regions, and depending on cultural values. Cultural differences also affect the perception of academic integrity in the world. It is noted that there are several problems with observance of the academic integrity in Ukraine. The attitude to the issues of academic integrity in Ukraine directly depends on the ethical principles and values in society and legal culture. It is concluded that the implementation of academic integrity values requires changes in the system of education and scientific activity in Ukraine. The academic community must be a true advocate of academic integrity and actively strive for its implementation in the everyday institutional life of its members. Universities, faculties and teachers have a significant role to play in communication, strengthening and securing values of academic integrity and policy of the educational institution, academic culture and legal culture in general. Today it is important for Ukrainian institutions not only to create policies, procedures and rules in the field of academic integrity but also to introduce them into the everyday life of the such institution, to constantly improve them, to form academic culture, legal culture and respect for the rule of law.

Проанализирован Рейтинг верховенства права за 2021 год, Рейтинг процветания за 2021 год, Рейтинг уровня образования по странам 2021 года, мировые рейтинги университетов (Times Higher Education за 2021 год, QS World University Rankings 2021), продемонстрировано существование четкой корреляции между соблюдением принципа верховенства права в государстве и правовой культуре, образованием и соблюдением академической добродетели. Доказано, что чем выше уровень соблюдения принципа верховенства права, тем выше уровень правовой культуры и, соответственно, уровень и качество образования и соблюдения академической добродетели. Освещены актуальные проблемы академической добродетели в Украине и предложены пути их решения.
Rule of law, legal culture, education and academic integrity
Дуліба, Є. В. Верховенство права, правова культура, освіта й академічна доброчесність / Євгенія Володимирівна Дуліба, Ольга Євгенівна Аврамова, Анатолій Миколайович Куліш, Валерія Валеріївна Миргород-Карпова // Вісник Харківського національного університету внутрішніх справ. – 2022. – № 3 (98). – С. 15-25. - DOI: https://doi.org/10.32631/v.2022.3.01.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; верховенство права; rule of law; правова культура; legal culture; правовая культура; академічна доброчесність; academic integrity; академическая добродетель; заклади освіти; учебные заведения; educational institutions; Україна. Ukraine. Украина; зарубіжні країни; foreign countries; зарубежные страны; якість освіти; quality of education; качество образования